2003
DOI: 10.1038/sj.bmt.1704153
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hematopoietic stem cell transplantation for breast cancer in Europe: critical evaluation of data from the European Group for Blood and Marrow Transplantation (EBMT) Registry 1990–1999

Abstract: Summary:The aim of this study was to identify trends in high-dose chemotherapy (HDC) with autologous hematopoietic stem cell transplantation (ASCT) and to assess survival in a large cohort of breast cancer (BC) patients receiving this therapy in Europe from 1990 to 1999. A total of 7471 patients who received HDC with ASCT between January 1, 1990 and December 31, 1999 were reported to the European Group for Blood and Marrow Transplantation Registry. Data required for demographics and survival analysis were avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 28 publications
1
31
0
1
Order By: Relevance
“…The European Group for Blood and Marrow Transplantation reviewed their registry data for the past decade. 11 The large series corroborates the individual trials, with a suggestion of improved survival. In contrast, the PBT-1 Study reported by Stadmauer et al 12 showed no differences in PFS or OS between high-dose chemotherapy with hematopoietic support compared with maintenance cyclophosphamide, methotrexate, and 5-fluorouracil (CMF) chemotherapy for women with metastatic breast cancer who responded to conventional induction chemotherapy.…”
Section: Introductionsupporting
confidence: 67%
“…The European Group for Blood and Marrow Transplantation reviewed their registry data for the past decade. 11 The large series corroborates the individual trials, with a suggestion of improved survival. In contrast, the PBT-1 Study reported by Stadmauer et al 12 showed no differences in PFS or OS between high-dose chemotherapy with hematopoietic support compared with maintenance cyclophosphamide, methotrexate, and 5-fluorouracil (CMF) chemotherapy for women with metastatic breast cancer who responded to conventional induction chemotherapy.…”
Section: Introductionsupporting
confidence: 67%
“…36 In our cohort of patients with MBC, women receiving HDC as consolidation therapy after achieving response to SDC had the best prognosis, confirming previous reports. 21,22,37 A significant proportion of such patients are long-term progression-free survivors. Importantly, HDC was effective in producing a CR in 20.4% of patients for whom SDC failed to produce CR; such patients having an outcome superimposable to patients transplanted in CR.…”
Section: Hdc For Metastatic Breast Cancer In Italy M Martino Et Almentioning
confidence: 99%
“…Median duration of growth factor administration until day of apheresis was 13 days (range, [10][11][12][13][14][15][16][17][18][19][20]. The number of days was less for the lenograstim arm with a median number of 12 days (range, 11-16) versus 13 days (range, 10-17) for the filgrastim arm and 14 days (range, [12][13][14][15][16][17][18][19][20] for the molgramostim arm (Po0.0001) ( Table 2).…”
Section: Patientsmentioning
confidence: 99%
“…11 One or more aphereses were performed until cumulative yield of CD34 þ cells was X2 Â 10 6 /kg, the threshold fixed to guarantee a safe hematological recovery. 12 The PBPC harvest was performed using the spectra COBE BCT, Aphaeresis System (Lakewood, CO, USA).…”
Section: Pbpc Collectionmentioning
confidence: 99%